Erratum: Free-standing supramolecular hydrogel objects by reaction-diffusion - Matija Lovrak (Nature Portfolio, 2017)
Nature Communications 8: Article number:15137 (2017); Published: 5 June 2017; Updated 30 June 2017 In the original HTML version of this Article, which was published on 5 June 2017, the publication date was incorrectly given as 5 July 2017. This has now been corrected in the HTML; the PDF version of the paper was correct from the time of publication.